2020
DOI: 10.18778/0867-5856.30.2.26
|View full text |Cite
|
Sign up to set email alerts
|

Exploring destination image, familiarity, information search behaviour, involvement and travel motivation as influencers of ecotourists’ destination loyalty

Abstract: This work aims at exploring the influence of selected factors that have received little attention in the past on ecotourism destination loyalty within the context of a developing country. The factors are destination image, familiarity, information search behaviour, involvement and travel motivation. The research was conducted on ecotourists visiting Malaysia who were approached on site and assisted to complete the survey instrument. The sample size was 813, representing a response rate of 47%. Hypotheses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 77 publications
1
6
0
Order By: Relevance
“…H2 predicted that guests more satisfied with low-carbon services from luxury hotels would be more likely to revisit, which is in line with previous research [167,168]. According to the survey, most guests (77.96%) were first-time visitors at the hotels.…”
Section: Discussionsupporting
confidence: 81%
“…H2 predicted that guests more satisfied with low-carbon services from luxury hotels would be more likely to revisit, which is in line with previous research [167,168]. According to the survey, most guests (77.96%) were first-time visitors at the hotels.…”
Section: Discussionsupporting
confidence: 81%
“…According to the results of our study, the degree of involvement in tourism programs is associated with rural tourism imagery, familiarity, motivation, and willingness. The investigators concluded that although tourism development has become a mature industry over a long period of time [60,61], due to its competitiveness, the high similarity of tourism characteristics in neighboring countries [29], and the impact of the COVID-19 epidemic, it has become the most important trend to create a brand image, increase tourists' attention to the scenic areas, and enhance travel ideas and motivation to facilitate the achievement of travel behavior [30].…”
Section: The Relationship Between Tourism Programs Tourists and Rural Sustainable Developmentmentioning
confidence: 99%
“…Furthermore, tourism activities must first stimulate tourists' imagination of tourist destinations to generate tourism attraction [51], and then produce tourism motivation [21,30], in order to stimulate people's desire to complete tourism motivation and realize their dreams of tourism planning.…”
Section: The Relationship Between Tourism Programs Tourists and Rural Sustainable Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in Mathematical Physics the feature representation of the fabric image to be retrieved with all the feature representations in the feature database, and finally output the result of fabric image retrieval. It involves two key technologies: image feature extraction technology and similarity matching technology [12]. The maturity of the image retrieval model-convolutional neural network (CNN) model has inspired scholars to solve the ideas in image retrieval, and a large number of results have been obtained through a large number of experiments.…”
Section: Multifeature Image Retrieval Techniquementioning
confidence: 99%